Rancang Bangun Sistem Informasi E-Commerce Kain Tenun Tanimbar Berbasis Web di Kota Ambon - Dessy Gloria Palyama; Pieter Leunupun; Refi Usmany (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
The development of information technology, particularly in e-commerce, is increasingly expanding into various sectors of education, economics, and business. In Ambon City, the Kudamati sub-district is one of the villages selling Tanimbar woven cloth, produced by housewives. Woven cloth sales are still conducted manually, requiring consumers to visit the location to complete the buying and selling process. Promotion still relies on lectures, and the lack of a marketing strategy hinders the broader reach and development of Tanimbar woven cloth's potential, particularly in terms of technology utilization. This research aims to design and build a web-based e-commerce information system using the Rapid Application Development (RAD) method. This system expands market reach, increases sales, simplifies ordering, and enhances productivity. The data processing process involves requirements planning, system design, development, and implementation. The system was developed using PHP and MySQL. Test results indicate that the system can support digital marketing of woven cloth, simplify consumer ordering, improve market access, and enhance the efficiency of Tanimbar woven cloth promotion.